Development of an Analytical Method for the Determination of Amoxicillin in Commercial Drugs and Wastewater Samples, and Assessing its Stability in Simulated Gastric Digestion - Unutkan, Tugce; Bakirdere, Sezgin; Keyf, Seyfullah (OXFORD UNIV PRESS INC, 2018)
A highly sensitive analytical HPLC-UV method was developed for the determination of amoxicillin in drugs and wastewater samples at a single wavelength (230 nm). In order to substantially predict the in vivo behavior of amoxicillin, drug samples were subjected to simulated gastric conditions. The calibration plot of the method was linear from 0.050 to 500 mg L-1 with a correlation coefficient of 0.9999. The limit of detection and limit of quantitation were found to be 16 and 54 mu g L-1, respectively. The percentage recovery of amoxicillin in wastewater was found to be 97.0 +/- 1.6%. The method was successfully applied for the qualitative and quantitative determination of amoxicillin in drug samples including tablets and suspensions.
Keywords: PERFORMANCE LIQUID-CHROMATOGRAPHY; CLAVULANIC ACID; PHARMACEUTICAL FORMULATIONS; BIOLOGICAL-FLUIDS; HPLC METHOD; ASSAY; AMOXYCILLIN; PLASMA; ANTIBIOTICS; SERUM; Biochemistry & Molecular Biology; Chemistry